Interactive Media Requirements for Elementary Solar System Education: A Needs Analysis Study - Fittari, Mustika; Suprapto , Nadi; Suryanti (Papanda Publisher, 2025)
Science learning, particularly on the topic of the solar system, involves a variety of conceptual understandings. The solar system material can be categorized into four types of concepts: abstract concepts (43%), concrete concepts (14%), abstract concepts with concrete examples (29%), and descriptive concepts (14%). Given the dominance of abstract consept, the role of interactive multimedia is essential in helping students develop a solid understanding of the subject matter. Interactive media-based learning is considered an essential innovation in science education, offering new ways to engage students and support conceptual comprehension through visual and interactive elements. This study aims to analyze the initial needs for interactive media in teaching the solar system as part of promoting innovative science learning. This research employed a qualitative descriptive method, utilizing both literature reviews and field observation as its primary data collection techniques. Data were gathered through teacher interviews, student questionnaires, and a review of relevant references. The findings revealed that students tend to prefer using interactive media in learning, and teachers also favor digital media in the classroom. However, the current use of digital media is still limited, mostly relying on PowerPoint presentations and online videos that are not specifically designed for the learning objectives.